Improving the academic writing capacity of nursing students as a means of contributing to scholarly work - Wa Ode Novi Angraeni; Suprapto Suprapto; Trimaya Cahya Mulat; Maria Kurni Menga (Edukasi Ilmiah Indonesia, 2025)
Academic writing is a fundamental skill that nursing students must develop to contribute effectively to the advancement of knowledge and evidence-based practice in healthcare. However, many students face challenges in organizing ideas, using appropriate scientific language, and understanding the structure of scholarly articles. This community service program aims to enhance nursing students' academic writing capacity through interactive workshops, hands-on mentoring sessions, and peer review activities. The program focuses on improving students’ ability to select relevant topics, conduct literature reviews, formulate research questions, and adhere to scientific writing conventions. The program's outcomes include increased student confidence in writing, improved quality of academic manuscripts, and a greater interest in publication and academic discourse. This initiative is expected to foster a culture of research and scholarly communication among nursing students, ultimately contributing to their educational and professional development